Decentralized day-ahead scheduling of multi-area integrated electricity and natural gas systems considering reserve optimization. (1st May 2020) - Wu, Gang; Xiang, Yue; Liu, Junyong; Gou, Jing; Shen, Xiaodong; Huang, Yuan; Jawad, Shafqat
Abstract: To maximize the benefits of multi-area cooperation and guarantee system reliability, a day-ahead scheduling model for multi-area integrated electricity and natural gas systems (IEGS) considering reserve optimization is proposed in this paper. The reserve scheduling is integrated into the multi-area optimal dispatch model to hedge against the risk caused by the uncertainties in electricity and gas systems. The reserve constraints in electricity and natural gas systems are modeled as probabilistic forms with a predefined confidence level based on chance-constrained programming (CCP). In order to protect the information privacy of each area, the original centralized energy-reserve co-optimization problems are decomposed into several area sub-problems that can be solved independently. Furthermore, the alternating direction method of multipliers (ADMM) with self-adaptive penalty parameters is adopted to solve the proposed model in a decentralized manner. The feasibility and effectiveness of the proposed models and methods are verified in a three-area IEGS. Highlights: An optimal scheduling model for multi-area IEGS is established. A probabilistic reserve scheme to cope with uncertainties is modeled. An ADMM based decentralized solution strategy is designed.